Cross-sectional survey of respiratory symptoms and exposures in Scottish health service cleaners. (19th October 2011) - Nasir, Syed; Sanchez-Vazquez, Manuel; Dick, Finlay
Abstract : Objectives: Health service cleaners play a key role in safeguarding patients' health. Limited research has been done on cleaners' workplace exposures and respiratory health. This study assessed the risk of asthma and chronic bronchitis among Scottish National Health Service (NHS) cleaners. Methods: A cross-sectional survey of NHS Highland Region cleaners and administrative staff (never employed as cleaners), aged 16–75 years. A questionnaire, based on the European Community Respiratory Health Survey questionnaire, explored respiratory symptoms and occupational exposures. Asthma was defined as reported symptoms in the last year or current use of drugs to treat asthma. Chronic bronchitis was defined as regular dry or productive cough at least 3 months a year, for at least 2 successive years. Pack-years of smoking data were sought. ORs with 95% CI were calculated using adjusted unconditional logistic regression. Results: The response rate was 55.5% (216 cleaners, 39.6%; 645 administrative staff, 62.2%). After adjusting for age and smoking, no significant differences were found between the occurrence of asthma and chronic bronchitis in cleaners compared to administrative staff: current asthma OR 1.21, 95% CI 0.77 to1.84; chronic bronchitis 1.52, 0.98 to 2.33). Conclusions: This study had sufficient power to detect a 9% difference in asthma and chronic bronchitis point prevalence between the groups. Previous studies found cleaners were at increased risk of asthma and COPD. Exposure controls for NHS Highland cleaners (staff training, careful selection of cleaning agents, no sprays) may account for these negative results.